Struktur Populasi Ikan Seluang (Rasbora argyrotaenia) di Hilir Sungai Sekadau Kecamatan Sekadau Hilir Kabupaten Sekadau - Ari Hepi Yanti, Fransiska Yeni Suryani, Tri Rima Setyawati (Jurnal Protobiont, 2019)
Rasbora argyrotaenia is one of the species of freshwater fish that found in downstream at the Sekadau river. The seluang fish population (R. argyrotaenia) river downstream is in danger of declining as a result of public activity. The goal of the study is to identify the structure of R. argyrotaenia populationÂ  and the chemical factors of the water downstream from the Sekadau River. Data extraction takes place between March and April 2018. Fish are found three times in three weeks at a week's interval of 1 week at a time. Studies show that seluang fish (R. argyrotaenia) were found up to 213 individuals of 69 individuals females, 58 individual males and 86 individual unidentified. The seluang fish that is most commonly found 2-6 cm by 131 individuals, and the smallest one at 12-16 cm size Â is 4 individuals. The gender ratio of male and female fish to the four stations is 1:1.